Screening of commercial meat products from supermarket chains for feline derivatives using SP-PCR-RLFP and lab-on-a-chip - Md. Al Amin; Rahman, Md. Mahfujur; Ahmad Razimi, Mohd Shahril; Chowdhury, Zaira Zaman; Md. Hussain, Muhammad Nasri; Mohd Desa, Mohd Nasir (Elsevier, 2020)
Determination of feline meat in food products is an important issue for social, health, economic and religious concern. Hence this paper documented the application of species specific polymerase chain reaction-restriction fragment length polymorphism (SP-PCR-RFLP) assay targeting a short-fragments (69 bp) of mitochondrial cytochrome b (cytb) gene to screen feline meat in commercial meat products using lab-on-a-chip. The SP-PCR assay proved its specificity theoretically and experimentally while testing with different common animal, aquatic and plant species of DNA. The feline specific (69 bp, 43- and 26-bp) characteristic molecular DNA pattern was observed by SP-PCR and RFLP analysis. For assay performance, it was tested in three different types of commercial dummy meat products such as frankfurters, nuggets and meatballs and digested with AluI-restriction enzyme. The highest sensitivity of the assay using lab-on-a-chip was as low as 0.1 pg or 0.01 % (w/w) in commercial dummy meat products. We have also applied this assay to screen three important commercial meat products of six different brand from six supermarket chains located at three different states of Malaysia. Thus total 378 samples were tested to validate the specificity, sensitivity, stability of the assay and utilization of it for commercial meat product screening.